Manic symptoms and impulsivity during bipolar depressive episodes - Swann, Alan C; Gerard Moeller, F; Steinberg, Joel L; Schneider, Laurie; Barratt, Ernest S; Dougherty, Donald M (Bipolar disorders, 2007)
Objectives:  In contrast to the extensive literature on the frequent occurrence of depressive symptoms in manic patients, there is little information about manic symptoms in bipolar depressions. Impulsivity is a prominent component of the manic syndrome, so manic features during depressive syndromes may be associated with impulsivity and its consequences, including increased risk of substance abuse and suicidal behavior. Therefore, we investigated the prevalence of manic symptoms and their relationships to impulsivity and clinical characteristics in patients with bipolar depressive episodes. Methods:  In 56 bipolar I or II depressed subjects, we investigated the presence of manic symptoms, using Mania Rating Scale (MRS) scores from the Schedule for Affective Disorders and Schizophrenia (SADS), and examined its association with other psychiatric symptoms (depression, anxiety, and psychosis), age of onset, history of alcohol and/or other substance abuse and of suicidal behavior, and measures of impulsivity. Results:  MRS ranged from 0 to 29 (25th–75th percentile, range 4–13), and correlated significantly with anxiety and psychosis, but not with depression, suggesting the superimposition of a separate psychopathological mechanism. Impulsivity and history of substance abuse, head trauma, or suicide attempt increased with increasing MRS. Receiver‐operating curve analysis showed that MRS could divide patients into two groups based on history of alcohol abuse and suicide attempt, with an inflection point corresponding to an MRS score of 6. Discussion:  Even modest manic symptoms during bipolar depressive episodes were associated with greater impulsivity, and with histories of alcohol abuse and suicide attempts. Manic symptoms during depressive episodes suggest the presence of a potentially dangerous combination of depression and impulsivity.